Risk Management Analysis of the Planet Gear Product at PT XYZ Batam - Hanselia, Ruth; Silviana, Cerryn; Ramadita, Chairani Nazwa; Meulia, Sri; Farawansya, Nurul Aulia (Journal of Collaborative Industrial Management (JCIM), 2025)
This study aims to identify and analyze the root causes of product defects in the injection molding process at PT XYZ Batam, particularly in bearing and pulley components. Defects such as oversized diameter (gate high), cracks (dented), burrs, and black spots from foreign particles were frequently found during production. The Fishbone Diagram method was used to systematically categorize the potential causes into four factors: Man, Machine, Method, and Material. Further analysis was conducted using the Failure Mode and Effect Analysis (FMEA) to assess each risk based on severity, occurrence, and detection scores. The gate high defect had the highest initial Risk Priority Number (RPN) of 36, indicating a high-risk level, followed by burrs with an RPN of 35. Risk mitigation strategies included machine recalibration, regular sharpening or replacement of cutting tools, implementation of standard operating procedures (SOPs), and daily cleaning and lubrication to prevent equipment breakdown. The results highlight the importance of consistent maintenance, structured documentation of production activities, and supervisory guidance to minimize the risk of recurring defects. Through the application of quality control tools such as Fishbone Diagram and FMEA, PT XYZ Batam can improve product reliability, reduce losses, and enhance operational efficiency in the competitive field of precision manufacturing.